Need-Based English Competency Development Strategies to Support MSME Product Internationalization Within the RPJMN Framework - Andrysyah Andrysyah; Siska Hasibuan; Ramadani Ramadani; Yeni Rachmawati; Prima Yanti Siregar; Heridayani Heridayani; Asri Sanusi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
This study investigated the English language needs and challenges faced by Indonesian Micro, Small, and Medium Enterprises (MSMEs) in preparing for international market expansion. Utilizing a mixed-method approach with quantitative surveys and qualitative thematic analysis guided by Miles, Huberman, and Saldaña (2014). The research design used multi-case or comparative study in 13 MSMEs in Sumatera Utara, Indonesia. This study employed a purposive sampling technique to select respondents who met specific criteria relevant to the research objectives. Data were collected through observation, questionnaires, and interviews. The observation focused on participants’ behavioral patterns and contextual interactions, while the questionnaire gathered quantitative data on respondents’ perceptions and attitudes. In addition, semi-structured interviews were conducted to obtain deeper qualitative insights into participants’ experiences. The quantitative data were analyzed using descriptive and inferential statistical methods to identify trends and relationships, whereas the qualitative data were analyzed through thematic analysis, involving data reduction, coding, categorization, and interpretation to draw meaningful conclusions. The findings revealed that MSMEs experience significant barriers in communicating with foreign buyers, particularly in conversational English, understanding export-import terminology, and preparing product descriptions, which hinders their export readiness. The study highlighted a strong demand for practical, context-specific English training materials aligned with MSME business types and operational needs. MSMEs express a clear preference for hands-on, simulation-based training methods over theoretical approaches, emphasizing the effectiveness of role-play and practice-based modules in enhancing communication competence. Digital platforms such as WhatsApp, Zoom, and YouTube are recognized as flexible and accessible media for delivering English training. Furthermore, there was a high expectation for government facilitation of affordable, structured, and sustainable English training programs tailored to export-oriented MSMEs